Synthesis, characterization and electrical conductivity of chitosan-pani/ MMT nanocomposite - DILLIP KUMAR BEHERA; KAMPAL MISHRA; P.L.NAYAK (International Journal of Pharma and Bio Sciences, 2017)
In this research programme Chitaniline nanocomposites has been synthesized by grafting the biopolymer Chitosan with Polyaniline and blended with Montmorillonite (MMT). The grafting process was carried out using ammonium persulfate in acidic medium. The chitaniline nanocomposites thus synthesized was characterized using various techniques like UV-visible spectroscopy, Fourier Transmission Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) techniques. The electrical conductivity of the nanocomposites was also measured.